2021
DOI: 10.3390/buildings11120668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Needle Type, Number of Layers on FPAFC Composite against Low-Velocity Projectile Impact

Abstract: Protective structures subjected to intensive loads that may benefit from the use of multilayer composite structures with excellent hardness and impact resistance represent an emerging research field in recent times. In this study, low-velocity projectile impact tests were performed on Functionally-graded Preplaced Aggregate Fibrous Concrete (FPAFC) mixtures to evaluate their performance. The effects of projectile needle type, fibre type and hybridization in addition to the number of layers in the composites on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Generally, several strategies are utilized to control temperature and prevent cracks in practical engineering, including the adoption of pre-cooling aggregate and ice water, a pipe cooling method by circulating cold water through internal pipes during the concrete hardening stage [11], and the usage of a certain dosage of fly ash [12][13][14][15], fibers [16][17][18][19][20][21][22][23], and a magnesia expansion agent (abbreviated as MgO thereafter) [24][25][26][27][28][29][30]. However, the pre-cooling method and pipe cooling method need some additional labor as well as more construction time and cost [11].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, several strategies are utilized to control temperature and prevent cracks in practical engineering, including the adoption of pre-cooling aggregate and ice water, a pipe cooling method by circulating cold water through internal pipes during the concrete hardening stage [11], and the usage of a certain dosage of fly ash [12][13][14][15], fibers [16][17][18][19][20][21][22][23], and a magnesia expansion agent (abbreviated as MgO thereafter) [24][25][26][27][28][29][30]. However, the pre-cooling method and pipe cooling method need some additional labor as well as more construction time and cost [11].…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that a 28% increase in absorbed impact energy may be achieved by the double-layered beam, compared to the similar single-layered beam with the same fibre quantity. Nandhu prasad et al [30] investigated the projectile impact performance of threelayered functionally graded preplaced aggregate fibrous concrete. Steel and polypropylene fibres were used in three layers with different dosages and hybrid combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Prasad et al [11] evaluated the performance of functionally graded preplaced aggregate fibrous concrete (FPAFC) via the low-velocity projectile impact tests. The bioinspiration of the excellent impact strength of turtle shells was used to design an FPAFC comprising a higher amount of steel and polypropylene fibers at the outer layers.…”
Section: Overview Of This Special Issuementioning
confidence: 99%